2017
DOI: 10.1136/bmjopen-2016-013150
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of current and secondhand smoking in Greece: results from the Global Adult Tobacco Survey (GATS) study

Abstract: ObjectivesGreece is one of the leading tobacco-producing countries in European Union, and every year over 19 000 Greeks die from tobacco-attributable diseases. The aim of the present study was to provide nationally representative estimates on current and secondhand smoking prevalence in Greece and their determinants.DesignCross-sectional.SettingGreece.ParticipantsA total of 4359 individuals participated in the Global Adult Tobacco Survey (GATS), a household survey of adults ≥15 years old (overall response rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
31
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 12 publications
6
31
1
2
Order By: Relevance
“…Specifically, the prevalence of smoking was quite low among the population aged ⩾65 years before the crisis and this has not changed in recent years [1]. Furthermore, according to a study conducted in the midst of the crisis, the prevalence of current smoking was found to increase with higher levels of education, especially in women, which is in contrast to the patterns of smoking in the West [67,71]. It is well known that in the western social context smoking is more prevalent among individuals with lower education [67,71].…”
Section: Respiratory Mortality In Greece Amid An Economic Crisismentioning
confidence: 82%
See 4 more Smart Citations
“…Specifically, the prevalence of smoking was quite low among the population aged ⩾65 years before the crisis and this has not changed in recent years [1]. Furthermore, according to a study conducted in the midst of the crisis, the prevalence of current smoking was found to increase with higher levels of education, especially in women, which is in contrast to the patterns of smoking in the West [67,71]. It is well known that in the western social context smoking is more prevalent among individuals with lower education [67,71].…”
Section: Respiratory Mortality In Greece Amid An Economic Crisismentioning
confidence: 82%
“…However, Greece is a leading tobacco-producing country in the context of the EU. It had the highest rate of tobacco consumption in the EU in 2010 [66,67], at 2458 cigarettes per capita [67]. In subsequent nationwide studies the prevalence of smoking was estimated to be 42.6%, 41%, 38.1% and 38.2% in 2008, 2010, 2011 and 2013, respectively [46,67,68].…”
Section: Respiratory Mortality In Greece Amid An Economic Crisismentioning
confidence: 99%
See 3 more Smart Citations